2022
DOI: 10.4103/jehp.jehp_1060_21
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioral determinants of early childhood caries

Abstract: BACKGROUND: Early childhood caries is like an epidemic, especially in the developing world, hence exploring its appropriate factors in causing the disease the need of the hour. Hence, the aim of the present study was to evaluate social and behavioral determinants of early childhood caries within the region of Ambala, Haryana. MATERIALS AND METHODS: The present survey elaborated oral examination among 398 study participants within the age group of 4–5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, 42 (85.7%) studies were cross-sectional in design [ 32 , 34 46 , 48 53 , 56 68 , 70 – 75 , 77 , 78 , 80 ], three were case-control [ 47 , 54 , 79 ] and four were cohort [ 33 , 55 , 69 , 76 ] studies. In addition, 42 (85.7%) studies were published in dental journals [ 32 , 33 , 36 38 , 41 48 , 53 – 80 ] and seven (14.3%) studies were published in non-dental journals [ 34 , 35 , 39 , 40 , 49 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 42 (85.7%) studies were cross-sectional in design [ 32 , 34 46 , 48 53 , 56 68 , 70 – 75 , 77 , 78 , 80 ], three were case-control [ 47 , 54 , 79 ] and four were cohort [ 33 , 55 , 69 , 76 ] studies. In addition, 42 (85.7%) studies were published in dental journals [ 32 , 33 , 36 38 , 41 48 , 53 – 80 ] and seven (14.3%) studies were published in non-dental journals [ 34 , 35 , 39 , 40 , 49 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 studies that identified an association between maternal and or paternal education and the prevalence of ECC, 13 (28.9%) identified and association between maternal [ 36 , 45 , 51 , 56 , 57 , 66 , 71 , 72 , 74 , 78 , 80 ], paternal [ 45 ] or parental [ 48 , 62 ] level of education and the severity of ECC. In addition, different levels of maternal and or paternal education were associated with ECC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation